(3GdebOeGJ GdeegOGJ deG GbJVg QShe GdeOhfI ef GdMcGe GdTQYjGJs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3aUd HGdWYGe Ydi ePgH eGdc hCUMGHg s
(3BNQgG (B:s
(3hHGddg GdJhajb hgh MSHG hfYe Gdhcjd hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(115) s
Keywords: (3Gdabg GdeGdcjs